(untitled) (Educação e Pesquisa, 2010)
The article presents results of an experiment in articulating the dimensions of gender, race, and social class in the study of the dynamics of schooling in Brazil based on the micro-data of the 2000 Demographic Census. The level of schooling is measured from the average years of study successfully completed by the population aged 10 or more. The study reveals that these three dimensions produce effects that cannot be simply added to each other, because they follow different logics. As we move from the older generations to the younger, women go from a situation of inferiority to one of superiority in terms of average years of schooling, whereas the black population maintains a position of inferiority in relation to the white population across all age groups, although with some reduction in the degree of inequality. In their turn, educational inequalities as related to the professional occupation, taken here as an indication of social class, appear as the most pronounced, both in male and female populations, and among blacks and whites. The text therefore reinforces the importance and possibility of articulating in the study of schooling the dimensions of gender, race, and social class, as recommended in the literature on the subject.